The Proficiency Of Oral Language And Phonological Awareness In Adult EFL Students - Fajar, Muh.; Aprilianto, Muhammad Haril; Heny Sulistyowati (Universitas PGRI Adi Buana Surabaya, 2023)
The ability to recognize phonological patterns is essential for comprehending language and word formation. The issues are brought on by the absence of an English sound in other languages, particularly in Indonesia. This study looked into the connection between oral language competency and phonological awareness in adult English language learners. Although additional in-depth studies on the relationship between phonological awareness and oral language ability in adult EFL learners have not been widely conducted, this is based on a curiosity about whether phonological awareness still has a relationship with it. Researchers employed a correlation design and quantitative approaches. Sixty-two respondents from the third-year STKIP PGRI Jombang students in the English Education department program participated in this study. Purposive approach was employed to choose the responders. The information is derived from the midterm exam assignments. The phonology and speaking lecturer created the tool for a semester four course on academic settings. With the use of SPSS version 25, non-parametric Spearman's rho was used to examine the data.According to the outcomes of the data analysis, the value of the 2-tailed sig. is 0.463, which is greater than 0.05.Therefore, the researchers draw the conclusion that there is no meaningful relationship between spoken language ability and phonological awareness. They assumed that the outcome was due to the disparity in emphasis between the speaking test scoring criteria and the course materials for Speaking for Academic Setting.